Quantification of particle-conjugated or particle-encapsulated peptides on interfering reagent backgrounds - Woon Teck Yap; W. Kelsey Song; Niharika Chauhan; P. Nina Scalise; Radhika Agarwal; Stephen D. Miller; Lonnie D. Shea (BioTechniques)
Particle-based technologies are increasingly being used in diagnostics and therapeutics. The particles employed in these applications are usually composed of polymers such as poly(lactide-co-glycolide) (PLG) and functionalized with peptides or proteins. Peptide or protein conjugation to particles is frequently achieved using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), while dimethyl sulfoxide (DMSO) is used to retrieve surface-attached or encapsulated peptides or proteins by solubilizing the particles. We examined strategies based on bicinchoninic acid (BSA), Coomassie Plus, and 3-(4-carboxybenzoyl)quinoline-2-carboxaldehyde (CBQCA) assays for the quantification of surface-attached or encapsulated peptides or proteins. We determined that the CBQCA assay is a highly sensitive and accurate substitute for radioactivity-based assays that is suitable for measuring multiple particle-bound or particle-encapsulated peptides or proteins in the presence of EDC or PLG in DMSO, compounds that interfere with the more commonly used BSA and Coomassie Plus assays. Our strategy enables the accurate quantification of peptides or proteins loaded onto or into particles—an essential component of particle-based platform design for diagnostics and therapeutics.